Asymmetric Information and Capital Structure: Empirical Evidence from Indonesia Stock Exchange - Mustaruddin, Mustaruddin; Dinata, Aristya; Wendy, Wendy; Azazi, Anwar (International Journal of Economics and Financial Issues, 2017)
This study is aimed to scrutinize the impact of asymmetric information on capital structure in Indonesia by taken the sample from firms listed in IDX with total of 225 observations. The capital structure is measured by Leverage (LEV) and the asymmetric information is measured by Amihud Illiquidity ratio (ILLQ) and firm size measured by book value of total assets (SIZE). In addition, two controlling variable of Altman Z-Score (ALT) and gross domestic product (GDP) are added. The data is analyzed by using multiple regressions with random effect panel data estimation. The results find that the impact of asymmetric information on capital structure is consistent before and after including controlling variables. The evidence is not robust to the inclusion of illiquidity ratio, whereas firm size is important in explaining on capital structure before and after including controlling variables. Keywords: Capital Structure, Asymmetric Information, Amihud Illiquidity, Firm Size, Altman Z-Score, Gross Domestic Product JEL Classification: G320